"Dando asas para borboletas": um estudo sobre o possível desenvolvimento espiritual na adolescência - Moreira, Mara Regina Franchin (2015)
Faced with so many transformations in the world in our century, be they in society, in philosophy, in sociology and in religion, it is challenging to talk about the human development in its most difficult phases, which are pre-adolescence and adolescence. Adolescents who ask: What is life and why am I living? Through an image of nature we compare their internal and external transformations with those of the metamorphosis of a caterpillar which transforms into a butterfly gaining wings to fly. How to help adolescents to face their existential questions and to develop in a healthy way in order to fly on the wings of the spirit? We describe the quest for spirituality as the main answer to all these questionings and we direct them to a spiritual itinerary in order to live out this spirituality in fullness: Flying on the Wings of the Spirit.